Insights into Grievance Mechanisms : Findings from a Survey of Grievance Focal Points in Project Implementation Units - World Bank (Washington, DC : World Bank, 2022)
In April and May 2020, a first-of-a-kind survey was conducted by the World Bank with project implementation unit (PIU) focal points responsible for the operation of grievance mechanisms (GMs) in World Bank-financed projects across the world. The aim of the survey was to better understand challenges and opportunities linked to GM design and implementation from the perspective of people on the frontline, and to identify areas where they may need additional support to guarantee an effective right to remedy in their projects. This note presents the rationale, methodology, and outcomes of this online survey, as well as related recommendations to improve the functioning of project-level GMs. First, details are provided regarding the background and implementation of the survey, followed by a presentation of survey results, main observations, and key messages regarding the current design and operating practices of GMs in World Bank-financed projects. The survey instrument itself is included in the appendix.